Penerapan Diversi Terhadap Anak Pelaku Penyalahguna Narkotika - Indrawati indrawati; Byrna Mirasari (University of Merdeka Malang, 2018)
This study examines the free application to the perpetrators of narcotics violations applied in the Banjarbaru District Court in accordance with various regulations relating to children’s rights such as Law No. 4 of 1949 concerning Child Welfare, Law No. 39 of 1999 concerning Human Rights, Law No. 35 of 2014 concerning Child Protection and Law No. 11 of 2012 concerning the Juvenile Justice System, including diversification requirements where the threat of punishment is less than 7 years and the perpetrator is not recidivism. Because that is true and true what hasbeen done by the facilitator of transfer / child judge in case Number 4 / Pid.Sus-Anak / 2016 / PN.BJB because it is in accordance with the rules relating to the transfer of those who transact with the law. Factors that hinder the adoption of a diversion attempt on children who abuse drugs in the Banjarbaru District Court are: Understanding of law enforcement officers involved in the Diversion process is still lacking. i.e. parties involved in the transfer process, such as Community / Bapas Supervisors including legal counsel / legal counsel who are interns, including juvenile judges, should be more familiar with the contents of Perma No. 4 of 2014 concerning the Guidelines for the Implementation of Diversification in the Child Criminal Justice System and the Role of Parents in the Transfer process are still less active due to a lack of understanding of the process.How to cite item: indrawati, I., Mirasari, B. (2018). Penerapan Diversi Terhadap Anak Pelaku Penyalahguna Narkotika. Jurnal Cakrawala Hukum, 9(2), 177-185. doi:https://doi.org/10.26905/idjch.v9i2.2764